Karen Education Department's multilingual education for language maintenance - Shee, Naw Khu (Kasetsart Journal of Social Sciences, 2018)
The choice of language of instruction and language policy in schools is a recent issue of concern with the maintenance of linguistic diversity through structured education in Myanmar. When multilingual societies adopt single-language-in-education policies, the trend is to assimilate different language speakers into that dominant language and their languages and cultures gradually decline and are lost. This sociolinguistic problem of the need to protect ethnic languages and cultures by integrating those languages and cultures into the education system is a signiﬁcant one confronting Myanmar. In this study, the focus was on micro-level practices along with the community-established policies to contribute to the current and ongoing national language in the education policy development process. This study drew on ﬁndings from documents review, in-depth interviews, focus group discussions, and classroom observations. The study included in its scope those Karen Education Department (KED) schools exclusively functioning in the Karen National Union (KNU)-controlled area in Myanmar. The study concerned the monolingual Sgaw Karen and did not investigate multilingual and multicultural student populations. This study showed that implementing language policies in education and applying strong mother tongue- based multilingual education (MTB-MLE) programs in the communities where there are predominantly ethnic people could result in the enhancement of the maintenance of ethnic languages for ethnic minorities.